A review of photovoltaic water pumping system designing methods, control strategies and field performance - Muhsen D.H.; Khatib T.; Nagi F. (Elsevier Ltd, 2023)
Artificial intelligence; Design; Numerical methods; Photovoltaic cells; Pumping plants; Pumps; Solar energy; Solar power generation; Artificial intelligent; Field performance; Incremental conductance; Load matching; Maximum Power Point Tracking algorithms; Photovoltaic systems; Photovoltaic water pumping; Water pumping systems; Maximum power point trackers